Kontribusi Bank Syariah Dalam Penguatan Ekonomi Lokal Berbasis UMKM - Dani Atmaja; Kusjuniati Kusjuniati (Kafalah: Jurnal Ekonomi, Manajemen, dan Keuangan Syariah, 2026)
MSMEs play an important role in strengthening local economies but face limited access to financing. Islamic banking serves as an alternative financial system based on justice and partnership principles. This study aims to analyze the contribution of Islamic banks to MSME-based local economic development. A qualitative literature review method is employed. The results show that Islamic banks contribute through sharia-based financing, business assistance, financial literacy education, and profit-sharing partnerships, which positively support MSME sustainability and local economic growth.